Increasing pattern of antibiotic resistance in Neisseria gonorrhoeae - Salam, Md. Abdus; Ahmed, Iftikhar; Sultan, Quazi Rakibus (Professional Medical Publications, 2005)
Objectives: To explore the fact of increasing pattern of resistance to commonly used antibiotics by Neisseria gonorrhoeae detected simultaneously in gram-stained smears and cultures of urethral and / or prostatic secretions. Design: Retrospective study to detect N. gonorrhoeae from the submitted urethral and / or prostatic secretions and their antibiogram. Subjects: One hundred thirty three male patients of suspected gonorrhoea attending the Skin & V.D. outpatients department of Rajshahi Medical College Hospital (RMCH), Bangladesh from January to November 2001. Setting: The study was conducted at the Department of Microbiology of Rajshahi Medical College as a part of its diagnostic service delivery to the patients of RMCH. Methods: Urethral and/or prostatic secretions were collected from the suspected cases of gonorrhoea. Gram-stained smears for microscopical detection of gram-negative diplococci and culture on Chocolate agar media were done for all samples. Antimicrobial susceptibility testing by standard disc diffusion method was performed using antibiotics commonly prescribed for the treatment of gonorrhoea. Results: Significant number of cases was found to be positive for N. gonorrhoeae in both urethral and prostatic secretions. As tools for detecting N. gonorrhoeae both Microscopical examination and Culture were equally comparable. Bacterial isolates showed around 11.60% resistant cases against Ciprofloxacin and Gentamycin while Penicillin and Amoxycillin were found to be least efficacious drugs. Cephalexin, Doxycycline & Tetracycline were equivocal in sensitivity. Conclusion: This study reinforces the microscopy of gram-stained smears as a good tool for rapid diagnosis of N gonorrhoeae. It also explores the fact of increasing pattern of antibiotic resistance by N. gonorrhoeae to commonly prescribing drugs.